AN EXPERIMENTAL STUDY OF THE KINETICS OF DECOMPRESSION-INDUCED CRYSTALLIZATION IN SILICIC MELT - Hammer J.E.; Rutherford M.J. (My University, 2002)
Experiments were conducted to study the temporal evolution of feldspar crystallization kinetics during isothermal decompression. Pinatubo dacite was held at 780°C, 220 MPa, fO2 = NNO + 2, H2O-saturated conditions for an equilibration period, decompressed to final pressures, Pf, ranging from 175 to 5 MPa, and then held for 0.3-931 hours. According to the plagioclase liquidus curve in PH2O-T space for the relevant melt composition, these decompressions impose effective undercoolings, ΔTeff, of 34-266°C. Growth of preexisting phenocrysts and newly formed sparse microlites dominate crystallization at 75 <= Pf < 150 MPa (ΔTeff = 34-93°C), and equilibrium crystal modes are achieved in <168 hours. Microlite nucleation is the dominant transformation process for 10 < Pf < 50 MPa (ΔTeff = 125-241°C), and chemical equilibrium is not attained by 168 hours under these conditions. Slow, steady decompressions typically produced normally zoned, euhedral, and planar-faceted feldspar crystals, although anhedral morphologies were produced at very low Pf. Contrary to expectation, slowly decompressed samples were usually further from chemical equilibrium than rapidly decompressed samples after similar durations below the initial pressure. Although counterintuitive, these trends are consistent with new constraints on the relative rates of feldspar nucleation and growth (controlled by ΔTeff and melt viscosity) experienced during each decompression path. Analysis of liquid to solid transformation kinetics using TTT-style diagrams shows that crystallization occurs most rapidly at ~100 MPa by a crystal growth mechanism. The next most efficient crystallization conditions are at 25 MPa, in a crystal nucleation-dominated regime.
Keywords: crystallization kinetics; microlites; Pinatubo dacite; textural analysis; crystal nucleation; crystal growth